The study of problem-solving abilities by digital games-based learning (DGBL) together with visual thinking; social studies for grade 1 students - Sirichokchaitrakool, Sirisukr; Boonpo, Piyanan; Srichinda, Manutchaya (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The purposes of this research were: 1) to design and develop learning management through the digital games-based as a base with visual thinking; 2) to study the students’ problem-solving ability; and 3) to study the learning achievement. The sample group was 39 students in grade 1 at Khon Kaen University Demonstration School Primary Level (Suksasart) in the first semester of the academic year 2023. The research tools were: 1) digital games-based learning with visual thinking as the learning management system and 2) a problem-solving ability test and a leaning achievement test. The statistics used for data analysis were percentage and mean. The results were as follows. 1) The result of the design of the digital games-based learning as a base is the design that enhances information retrieval for the students including the stable navigators with the similar structure, the visual graphics and font size which grabbed attention and were easy to read. The content and illustrations were corresponding and promoted the students to be able find out the solution to the problems given. The information was well-categorized which was intelligible and encouraged meaningful learning. The students had an opportunity to engage, brainstorm and solve the problems collaboratively. 2) The average score of the students’ problem-solving skills was 16.50 points, or 82.50% and there were 35 students which equal to 89.74% passed the criterion which expected 70%. Finally, 3) The average score of learning achievement scores was 15.50 or 77.50% and there were 33 students which equal to 84.61%, passed the criterion which expected 70%.